Основи формування інвестиційно-інноваційної стратегії розвитку залізничного транспорту - Полішко, Тетяна Валеріївна; Гребенюк, Галина Михайлівна (ТОВ «ДКС Центр», 2025)
UKR: У статті досліджено основи формування інвестиційно-інноваційної стратегії залізничного транспорту. Визначено, що економічний розвиток транспортних підприємств та саме їх існування в умовах розвитку ринкових відносин безпосередньо залежить від розробки стратегії розвитку підприємства, без якої підприємство не може вижити в сучасних умовах. Проблема забезпечення економічної безпеки держави залежить від оновлення і адаптації базових галузей, до яких належать підприємства залізничного транспорту. Підкреслена доцільність впровадження інвестиційної моделі розвитку на інноваційній основі; розмежування функцій державного регулювання та господарської діяльності залізничного транспорту; подальший розвиток конкурентного середовища; поетапне припинення перехресного субсидіювання пасажирських перевезень; здійснення комплексу заходів з удосконалення тарифної політики; створення ефективної системи управління галуззю; вдосконалення організаційної системи залізничного транспорту; забезпечення прозорості фінансової діяльності; підвищення мотивації праці; створення організаційно-правових економічних і техніко-технологічних передумов для впровадження принципів європейської транспортної політики.

ENG: The article examines the foundations of the formation of an investment and innovation strategy for railway transport. It is determined that the economic development of transport enterprises and their very existence in the conditions of the development of market relations directly depends on the development of an enterprise development strategy, without which the enterprise cannot survive in modern conditions. The problem of ensuring the economic security of the state depends on the renewal and adaptation of the basic industries to which railway transport enterprises belong. The expediency of implementing an investment model of development on an innovative basis is emphasized; the separation of the functions of state regulation and economic activity of railway transport; further development of the competitive environment; the gradual cessation of cross-subsidization of passenger transportation; the implementation of a set of measures to improve tariff policy; the creation of an effective industry management system; the improvement of the organizational system of railway transport; ensuring transparency of financial activities; increasing labor motivation; the creation of organizational and legal economic and technical and technological prerequisites for the implementation of the principles of European transport policy. The investment and innovation strategy should become the basis and at the same time a tool for effective long-term development of railway transport in Ukraine, to solve promising economic problems and achieve major socially significant results. Constant monitoring of all external and internal factors that directly affect transport flows, and building strategies on this basis, as well as their adjustment, if necessary, will allow Ukraine to achieve high economic results. Improving the quality of services, updating rolling stock, modernizing technologies, and improving management and organizational systems will allow the country's railways to adapt to market requirements, reduce costs, and stabilize financial and economic performance.
Fundamentals of Forming an Investment and Innovation Strategy for the Development of Railway Transport
Т. Полішко: ORCID 0000-0001-5773-4927; Г. Гребенюк: ORCID 0000-0002-2807-0268
Keywords: стратегія; інвестиції; інновації; розвиток залізничного транспорту; strategy; investments; innovations; development of railway transport; КЕМ ДІІТ; SOCIAL SCIENCES; SOCIAL SCIENCES:: Business and economics